Benznidazole therapy modulates Interferon-γ and M2 Muscarinic receptor autoantibody responses in Trypanosoma cruzi-Infected children - Cutrullis, Romina A. (2011)
Fil: Cutrullis, Romina A. Hospital de Niños Ricardo Gutiérrez. Servicio de Parasitología y Enfermedad de Chagas; Argentina.